Non-legacy contamination by 3,3'-dichlorobiphenyl in marine species: comparison between Mediterranean area and Antarctic region - PIZZINI, Sarah; Sbicego, Chiara; Grotti, Marco; COZZI, Giulio; PIAZZA, Rossano (Università degli Studi di Messina, 2016)
Polychlorinated biphenyls (PCBs) are among the main classes of persistent organic pollutants (POPs) and are largely distributed in every environmental compartment worldwide. The sources of PCB contamination are commonly associated to the industrial use of commercial mixtures, such as Aroclors, which were banned from production in 1979. However, different sources of PCBs, unrelated to the commercial distribution of mixtures, have been recently identified. In particular, the congener 3,3’-dichlorobiphenyl (PCB-11) has been considered as a marker of non-Aroclor PCB contamination in the environment [1,2]. Along with the other lower chlorinated congeners, PCB-11 is significantly affected by long-range atmospheric transport (LRAT) and has been found in almost every environmental matrix worldwide, including Polar regions. Despite the concern and the evidence about the global distribution of non-legacy PCB contamination, little is known about the potential adverse health effects of PCB-11 and its uptake through the food chain. The first aim of this work is to investigate and quantify the presence of the PCB-11 congener in samples of bivalves as an indication of non-legacy PCB contamination in biota matrices. A parallel analysis of bioaccumulation in Mediterranean and Antarctic samples is also presented. We used M. galloprovincialis and V. philippinarum, collected from the northern Adriatic coasts, and the Antarctic scallop A. colbecki, collected from Terra Nova Bay (Ross Sea, Northern Victoria Land) and stored in the Antarctic Environmental Specimen Bank, in order to compare the levels of PCB-11 in areas of high anthropogenic impact to those found in remote regions. [1] E. Grossman, Environmental Health Perspectives 121(2013) A87-93. [2] L.A. Rodenburg, J. Guo, S. Du, G. J. Cavallo, Environmental Science & Technology 44 (2010) 2816-21.